2000
DOI: 10.1007/s005860000182
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous transpedicular vertebroplasty with PMMA: operative technique and early results

Abstract: Vertebroplasty-percutaneous cement augmentation of osteoporotic vertebrae is an efficient procedure for the treatment of painful vertebral fractures. From a prospectively monitored series of 70 patients with 193 augmented vertebrae for osteoporotic and metastatic lesions, we analysed a group of 17 patients suffering from back pain due to osteoporotic fractures. The reinforcement of 45 vertebral bodies in these patients led to a significant and lasting pain reduction (P < 0.01 ). The presented technique is usef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
192
4
22

Year Published

2006
2006
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 393 publications
(220 citation statements)
references
References 15 publications
2
192
4
22
Order By: Relevance
“…In addition to the cause of the leakage, the differing cement leakage measurements influenced the results. Heini et al [16] provided further evidence that little cement leakage is found by standard X-ray imaging, whereas high rates are observed with computed tomography. Therefore, the GRADE evidence quality for cement leakage was very low because of the high risk of publication bias and outcome inconsistencies.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In addition to the cause of the leakage, the differing cement leakage measurements influenced the results. Heini et al [16] provided further evidence that little cement leakage is found by standard X-ray imaging, whereas high rates are observed with computed tomography. Therefore, the GRADE evidence quality for cement leakage was very low because of the high risk of publication bias and outcome inconsistencies.…”
Section: Discussionmentioning
confidence: 99%
“…Belkoff et al [3,4] provided evidence of pain reduction that was attributable to immobility and inhibition of micromovement in the fractured fragment. In addition, a cytotoxic effect of polymethylmethacrylate (PMAA) causes damage to terminal nerve endings and contributes to pain reduction [16]. However, Togawa et al [46] reported that PMAA did not influence the thermic pain reduction effect.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Since then, indications were extended to spinal column metastatic lesions, myelomas and acute vertebral fractures. During the past decades there has been adequate evidence in support of its safety, immediate pain reduction effectiveness exceeds 90% of cases and biomechanical stability [17][18][19][20][21]. Anyway, patient selection criteria and precise indications about timing of treatment for osteoporotic vertebral fractures have not been established yet.…”
Section: Discussionmentioning
confidence: 99%